What drives retailer loyalty? A meta-analysis of the role of cognitive, affective, and social factors across five decades - Liu-Thompkins, Yuping; Khoshghadam, Leila; Attar Shoushtari, Arjang; Zal, Saeed (Journal of Retailing, 2022)
Today's retailers face significant competition due to the proliferation of both retail formats and channels. It is crucial for retailers to understand how to develop a loyal customer base for competitive advantage. To this end, we conducted a meta-analysis of 1,908 effect sizes from 319 studies on retailer loyalty over the last 50 years, to examine the impact of cognitive, affective, and social retail experience on customer loyalty toward a retailer. Our analysis shows that affective experience became more important over time and had the highest impact on retailer loyalty, 24% more than that of social drivers and 50% more than cognitive drivers. Affective experience is particularly impactful online and for retailers of hedonic or low-involvement products. Social drivers increased significantly in impact over time too. Its effect was particularly strong on attitudinal loyalty, for studies with a higher proportion of females, and surprisingly, in utilitarian rather than hedonic retail contexts. Taken together, our findings suggest that traditional cognitive differentiators such as price and product assortment are no longer sufficient for maintaining customer loyalty to a retailer. Positive affective and/or social experience represent a more defensible path toward customer loyalty.
Keywords: affect; cognition; dept.mrk; meta-analysis; peer-reviewed; retailer loyalty; retailing; social interaction

A longitudinal reliability study of a consumer disidentification model - Prince, M.; Kwak, L. (Journal of Empirical Generalisations in Marketing Science, 2022)
Josiassen (2011) in a single cross-sectional survey investigated causal relations between consumer disidentification and domestic product judgments. The primary purpose of this replication paper is to evaluate the reliabilities of construct levels, as well as the significance, direction and magnitude of causal effects advanced in the original published structural model. The study measures relations between consumer disidentification (CDI) and domestic product judgments of American products over an extended 16 months period among second generation immigrants. In the present research the original CDI model fit was found to be longitudinally consistent and stable. Serendipitously, findings of the present study disclosed that over time baseline levels of consumer disidentification vary and actually declined significantly. Additionally, the negative effect of consumer disidentification on American product judgments significantly weakened over the course of the study. As an additional test of consumer predisposition reliability over time, the model in this study incorporated consumer xenocentrism (XEN) as a second predictor variable of domestic product judgments. Findings of this analysis were consistent with those found for CDI. These new phenomena have important theoretical and managerial implications. © 2022, University of South Australia. All rights reserved.
Keywords: dept.mkt; peer-reviewed; ⛔ No DOI found